The Potential of Implementing Smart Personal Protective Equipment (PPE) To Minimize Work Related Injuries in Construction Sites - Lee, Benny, Hai Chim*; Chang, Yee Ting; Fo, Kee Wah*; Kong, Sio Kah* (INTI International University, 2020)
Construction accidents has earned a bad reputation along the years even with personal protective equipment (PPE) provided on site. Wearable technology has become more common nowadays for preventing workplace injuries, ensuring level of safety in the workplace. Smart personal protective equipment (PPE) refers to PPE that connects to the internet and other devices like software or tablets to deliver real-time safety information. Hence, the aim for this research is to study the possibility of implementing smart personal protective equipment (PPE) in Malaysian construction industry. The findings show that majority of respondents are aware of construction accident, smart PPE are better in reducing injuries than conventional PPE and respondents are willing to implement in their company if Smart PPE is available in the market and the cost is reasonable.